Gender balance at work: A study of an Irish Civil Service department - Shannen Enright; Helen Russell (The Economic and Social Research Institute (ESRI), 2020)
While men occupy the majority of senior positions in the Civil Service, they are more likely than women to perceive gender bias in promotional competitions, according to an ESRI study. The study draws on survey responses from 904 Civil Servants within the Department of Agriculture, Food and the Marine (DAFM) from 2018, as well as administrative data from the Department. DAFM has been actively involved in dealing with the challenge of gender balance in their Department, and the 2018 survey was undertaken as a means of determining the road map for future action. The report examines gender differences in flexible working, promotions, training, and networking.
Keywords: 330; Gleichberechtigung; Führungskräfte; Öffentlicher Dienst; Erhebungstechnik; Irland